Axial compressive behavior and confinement mechanism of circular FRP-steel tubed concrete stub columns. (15th January 2021) - Wang, Yanlei; Chen, Guipeng; Wan, Baolin; Han, Baoguo; Ran, Jianghua
Abstract: Fiber-reinforced polymer (FRP)-steel tubed concrete (FSTC) columns have emerged as a new type of compression members. An experimental program was performed to further demonstrate the axial compressive behavior of FSTC stub columns and to clarify the confinement mechanism in such members. The test results showed that the capacities of the axially loaded FSTC specimens were enhanced with the increase of the FRP confinement and the decrease of the steel tube's diameter-to-thickness ( D / t ) ratio. After deducting the steel tube's axial bearing contribution through elastic–plastic analysis, the concrete cores' axial load–strain responses had a bilinear shape, which was very similar to the axial load–strain responses of the composite columns. Based on the comparison between steel confinement and FRP confinement, a confinement mechanism was proposed to reveal the interaction between the inner concrete core and the outer FRP-steel composite tube. It was divided into three stages: domination of steel confinement, domination of FRP-steel dual confinement, and domination of FRP confinement. The total confining pressure at the third stage could be considered as a translational motion of the FRP confining pressure, which explained why the second stiffness of the confined concrete was more sensitive to the FRP confinement stiffness than the steel confinement.